Coupling of Methanol and Carbon Monoxide over H‐ZSM‐5 to Form Aromatics. Issue 38 (28th August 2018) - Chen, Zhiyang; Ni, Youming; Zhi, Yuchun; Wen, Fuli; Zhou, Ziqiao; Wei, Yingxu; Zhu, Wenliang; Liu, Zhongmin
Abstract: The conversion of methanol into aromatics over unmodified H‐ZSM‐5 zeolite is generally not high because the hydrogen transfer reaction results in alkane formation. Now circa 80 % aromatics selectivity for the coupling reaction of methanol and carbon monoxide over H‐ZSM‐5 is reported. Carbonyl compounds and methyl‐2‐cyclopenten‐1‐ones (MCPOs), which were detected in the products and catalysts, respectively, are considered as intermediates. The latter species can be synthesized from the former species and olefins. 13 C isotope tracing and 13 C liquid‐state NMR results confirmed that the carbon atoms of CO molecules were incorporated into MCPOs and aromatic rings. A new aromatization mechanism that involves the formation of the above intermediates and co‐occurs with a dramatically decreased hydrogen transfer reaction is proposed. A portion of the carbons in CO molecules are incorporated into aromatic, which is of great significance for industrial applications. Abstract : Aromatics with 80 % selectivity were obtained for the coupling of methanol and CO over H‐ZSM‐5. Carbonyl compounds and methyl‐2‐cyclopenten‐1‐ones (MCPOs) act as the intermediates to form aromatics. An aromatization mechanism is proposed that involves the formation of the above intermediates and co‐occurs with a dramatically decreased hydrogen transfer reaction.